Characterisation of ballistic carbon nanotube field-effect transistor - Sanudin, Rahmat (2005)
Scaling process of silicon transistor, particularly MOSFET, in the past decades had increased the perfonnance of silicon transistor with reduction of its size. However, the scaling process will eventually reaches its limit and by that time a new group of devices are expected to replace MOSFET in digital applications. This group of devices, known as nanoelectronic devices, is expected to offer better device geometry in nanometre scale with superior perfonnance. Carbon nanotube fieldeffect transistor (CNFET), one of nanoelectronic devices, is a transistor with its channel is made of carbon nanotube and it is designed to provide the solution for scaling process and the possibility of coexistence with current silicon technology. The purpose of this project is to study the behaviour ofCNFET and the main focus is on the simulation of its current-voltage (I-V) characteristic. The simulation study is carried out using MATLAB program and the result obtained is used to compare the device performance with MOSFET. Further analysis is also made to see the effect of oxide thickness and carbon nanotube diameter on the device perfonnance, in particular the drain current. From the simulation study, it is concluded that the perfonnance of CNFET has no significant advantage over MOSFET and its perfonnance is also affected by both nanotube diameter and oxide thickness.